Nutritional cares in chronic pancreatitis: an update - Santiago Silva, Clariana; Silvia Frangella, Vera (O Mundo da Saúde, 2009)
Chronic pancreatitis (CP) is characterized by anatomical injuries of an irreversible character and many times in a progressive way. Its incidence is esteem enters the 5 10/100,000 individuals per year, being its therapeutic care a high cost one. Alcohol is its main etiology. Nutritional care in CP is considered a challenge due to the presence of hypercatabolism, endocrine and exocrine dysfunctions and malnutrition. The objective of this study was to describe the current recommendations on nutritional cares of these individuals made by literature. It was elaborated from a systematic survey of works published since 1997, using a Boolean technique and searches in electronic sites of scientific trustworthiness. Results emphasize that nutritional evaluation of these individuals must consider a condition of weight loss throughout time, and anthropometric and laboratorial values. Dietary instructions and medication used are efficient in the treatment of 80% of cases. Recommended diet goes from normoproteic to hyperproteic (1.0-1.5g/kg/day), normoglucidic (with restrictions in cases of hyperglycemia or diabetes) and normolipidic (30% of lipids). The main source of lipids has vegetal origin, being indicated the use of Medium Chain Triglycerides (MCT) in cases of steatorhea. One must be alert as to the needs of vitamins supplementation of (especially liposoluble ones) and minerals, especially Calcium, Magnesium and Zinc. One concluded that there is no consensus in the literature regarding the established amounts of fibers; the recommended amount when MCTs are used and dietary behavior in azotorrhea cases. More studies for understanding the pathogenesis of this illness are necessary in order to contribute to its prevention and the development of new more specific and efficient therapies, especially dietary, in the care of this population.